Active pixel imagers incorporating pixel-level amplifiers based on polycrystalline-silicon thin-film transistors - El-Mohri, Youcef (American Association of Physicists in Medicine, 2009)
Active matrix, flat-panel imagers (AMFPIs) employing a 2D matrix of a-Si addressing TFTs have become ubiquitous in many x-ray imaging applications due to their numerous advantages. However, under conditions of low exposures and∕or high spatial resolution, their signal-to-noise performance is constrained by the modest system gain relative to the electronic additive noise. In this article, a strategy for overcoming this limitation through the incorporation of in-pixel amplification circuits, referred to as active pixel (AP) architectures, using polycrystalline-silicon (poly-Si) TFTs is reported. Compared to a-Si, poly-Si offers substantially higher mobilities, enabling higher TFT currents and the possibility of sophisticated AP designs based on both n- and p-channel TFTs. Three prototype indirect detection arrays employing poly-Si TFTs and a continuous a-Si photodiode structure were characterized. The prototypes consist of an array (PSI-1) that employs a pixel architecture with a single TFT, as well as two arrays (PSI-2 and PSI-3) that employ AP architectures based on three and five TFTs, respectively. While PSI-1 serves as a reference with a design similar to that of conventional AMFPI arrays, PSI-2 and PSI-3 incorporate additional in-pixel amplification circuitry. Compared to PSI-1, results of x-ray sensitivity demonstrate signal gains of ∼10.7 and 20.9 for PSI-2 and PSI-3, respectively. These values are in reasonable agreement with design expectations, demonstrating that poly-Si AP circuits can be tailored to provide a desired level of signal gain. PSI-2 exhibits the same high levels of charge trapping as those observed for PSI-1 and other conventional arrays employing a continuous photodiode structure. For PSI-3, charge trapping was found to be significantly lower and largely independent of the bias voltage applied across the photodiode. MTF results indicate that the use of a continuous photodiode structure in PSI-1, PSI-2, and PSI-3 results in optical fill factors that are close to unity. In addition, the greater complexity of PSI-2 and PSI-3 pixel circuits, compared to that of PSI-1, has no observable effect on spatial resolution. Both PSI-2 and PSI-3 exhibit high levels of additive noise, resulting in no net improvement in the signal-to-noise performance of these early prototypes compared to conventional AMFPIs. However, faster readout rates, coupled with implementation of multiple sampling protocols allowed by the nondestructive nature of pixel readout, resulted in a significantly lower noise level of ∼560 e (rms) for PSI-3.